Musings in the museum Celebrating the centenary of the Chhatrapati Shivaji Maharaj Vastu Sangrahalaya formerly the prince of wales museum of western India - Dehejia, Harsha V. (New Delhi Niyogi Books, 2022)
The journey of our icons the beauty of sharira